1993
DOI: 10.1080/02699939308409192
|View full text |Cite
|
Sign up to set email alerts
|

Studying the emotion-antecedent appraisal process: An expert system approach

Abstract: The surprising convergence between independently developed appraisal theories of emotion elicitation and differentiation is briefly reviewed. It is argued that three problems are responsible for the lack of more widespread acceptance of such theories: (1) the criticism of excessive cognitivism raised by psychologists working on affective phenomena; (2) the lack of process orientation in linking appraisal to the complex unfolding of emotion episodes over time; and (3) the lack of consensus on the number and typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
251
0
14

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(273 citation statements)
references
References 32 publications
8
251
0
14
Order By: Relevance
“…246-247, 262;Scherer, 1993Scherer, , 2001aSmith & Lazarus, 1993, pp. 263-264;Stein & Levine, 1989, 1990.…”
Section: Coping Potentialmentioning
confidence: 99%
“…246-247, 262;Scherer, 1993Scherer, , 2001aSmith & Lazarus, 1993, pp. 263-264;Stein & Levine, 1989, 1990.…”
Section: Coping Potentialmentioning
confidence: 99%
“…The appraisal of goal-obstacle or goal-blocking is generally accepted as an important determinant of anger as well as aggression. Besides its key role in the influential frustration Áaggression hypothesis (Dollard, Doob, Miller, Mowrer, & Sears;1939), it has also been adopted under various forms by numerous more recent appraisal theorists as a major 1 Some appraisal theories also hypothesise that the appraisal of power or control is an important determinant of anger (e.g., Roseman et al, 1990;Scherer, 1993). This appraisal was not included in the present study because empirical evidence so far has failed to show a consistent association between this appraisal and anger (see, e.g., Kuppens, Van Mechelen, Smits, & De Boeck, 2003) and in the present study we wanted to include only those appraisals that have been proven to be predictive for anger.…”
Section: Central Appraisals Of Angermentioning
confidence: 99%
“…This appraisal was not included in the present study because empirical evidence so far has failed to show a consistent association between this appraisal and anger (see, e.g., Kuppens, Van Mechelen, Smits, & De Boeck, 2003) and in the present study we wanted to include only those appraisals that have been proven to be predictive for anger. component of anger and anger-like emotions; the latter include frustration (Averill, 1982), perceived goal-obstacle (Ellsworth & Smith, 1988;Smith & Ellsworth, 1985), motivational incongruence (Smith & Lazarus, 1993), motive inconsistency (Roseman et al, 1990), undesirable event (Ortony et al, 1988), goal obstructiveness (Scherer, 1993), and goal blocking (Izard, 1977).…”
Section: Central Appraisals Of Angermentioning
confidence: 99%
“…Building on the "Cognitive Appraisal Theory" (Roseman, 1991;Scherer, 1993), which has also been used in other political communication studies (Aarøe, 2011;Gross & D'Ambrosio, 2004), it has been shown that evaluations and interpretations of stimuli determine emotional responses (Moors, 2013). Such appraisals, which relate to goal congruence, certainty, perceived cause (self, other, circumstantial), and coping potential, determine the kind of emotion that will be experienced.…”
Section: Opinionated News and The Consequences Of The Hostile Media Pmentioning
confidence: 99%